A scoping review of innovations that promote interprofessional collaboration (IPC) in primary care for older adults living with age-related chronic disease in rural areas - Valerie Elliot; Julie Kosteniuk; Duane P. Minish; Chelsie Cameron; Megan E. O’Connell; Debra Morgan (PLoS ONE, 2025)
Background and objectives An aging population and associated multi-morbid chronic diseases (CDs) require comprehensive health care across multiple disciplines. Literature suggests interprofessional collaboration (IPC) in primary care is effective for CD models of care. However, IPC requires innovative implementation, particularly in rural and remote areas where access to health care services and providers is often limited. Our main objective was to identify and synthesize the available research evidence on innovations that promote IPC in primary care for older rural adults with CD, identify gaps in the literature, and provide recommendations for future research. Methods Comprehensive and systematic searches were conducted across four scientific databases for peer-reviewed, original research published in English since 1990, resulting in 9,343 records. Following elimination of duplicates, screening, and evaluation, 38 studies were included for synthesis. All studies were described and illustrated by frequency distribution, and findings were grouped thematically. Results Most innovations involved case management and focused on diabetes (n = 15), dementia (n = 12), and hypertension (n = 10). Rural challenges were more prevalent than benefits and mainly involved limited services and resources, while strengths were mainly related to close-knit connections and familiarity with one another. Three main themes regarding benefits of the innovations were: 1) enhanced availability/accessibility, 2) earlier detection/management/support, and 3) improved care. Subthemes included: 2a) education/support, 2b) CD or risk factor outcomes, 3a) care continuity, and 3b) care coordination. Five main gaps in the literature included few studies with age-related CDs other than diabetes, dementia, and hypertension; conducted outside of United States and Canada; randomized controlled trial (RCT) and longitudinal studies; that involved virtual or technology-assisted innovations; and that considered sex and gender in the analysis. Conclusions Several main areas were highlighted including rural strengths and challenges that impacted the innovations, key innovation benefits, and gaps in the literature. Recommendations for future research were made.